Ranchero [large type] - Gavin, Rick (Thorndike Press large print mystery series., 2012)
Repo man Nick Reid had a seemingly simple job to do: talk to Percy Dwayne Dubois about the payments he's behind on a flat screen TV, or repossess it. But Percy Dwayne hit Nick over the head with a shovel, tied him up with a lamp cord, and stole the mint-condition calypso coral-colored 1969 Ranchero that Nick had borrowed from his landlady. Nick will do anything to get the Ranchero back. And it turns out he might have to.